STRATEGI KAMPANYE CALON LEGISLATIF PEREMPUAN MENJELANG PEMILIHAN LEGISLATIF 2014 DI KOTA SEMARANG - Ofriendly Sagala; Fitriyah .; Lusia Astrika (Journal of Politic and Government Studies, 2015)
Abstract:Facing the legislative elections in the city of Semarang, 2014, intense political efforts made by the political parties for the sake of smoothing step pitch candidates to parliament. It is necessary to establish a strategy for women candidates success in winning people's voices. Besides a caleh must be able to understand and provide appropriate solutions related problems faced, automatic vast potential women candidates win the heart of the community. Researchers using Qualitative Research Methods and methods of data collection with interviews and documentation. The results showed that there are (4) four campaign strategy used by female legislators in Parliament Semarang in Pileg gain the most votes in 2014 and the strategy of the use of mass media, strategies to interact directly with the public, strategies directly participate in community activities and strategies rely on the role of a successful team in the campaign. Keywords: Campaign Strategy, Victory Strategies, Women Campaign